Analisis Partisipasi Digital Berbasis Kerangka E-Participation UNDP: Studi pada Aplikasi Laksa Kota Tangerang - Reyzah Zafira Widya Leyn; Yudi Muhtadi; Eko Prasetyo (Policy, Law and Political Research Center, 2025)
This study aims to understand the utilization of the LAKSA application as a means of digital participation and the optimization strategies employed by the Tangerang City Health Office. The challenges faced include a lack of public awareness regarding the application, digital literacy gaps, system limitations regarding responsiveness and real-time capabilities, minimal feedback, and insufficient socialization. This research employs a qualitative method with a descriptive approach. The theoretical framework utilized is the Digital Participation theory by the United Nations Development Programme (UNDP), encompassing e-information, e-consultation, and e-decision making. The findings reveal the absence of e-decision making indicators, where public aspirations serve merely as reports without involvement in health policy formulation. The primary barriers identified are the lack of real-time system responsiveness and the digital literacy gap among users. Offering novelty to the field, this study formulates an optimization strategy through the integration of thematic questionnaire features and the utilization of Artificial Intelligence (AI) to accelerate aspiration analysis. This strategy is recommended to transform LAKSA from a mere complaint channel into a substantive instrument for policy participation.